The Relationship Between Platelet and Lymphocyte Ratios and Left Atrial Thrombus Formation in Patients with Severe Mitral Stenosis due to Rheumatic Heart Disease at Haji Adam Malik Hospital Medan - Ramzi, Defriyan; Hasan, Harris; Raynaldo, Abdul Halim (Journal of Society Medicine, 2025)
Introduction: Rheumatic heart disease is an immune disease condition that often causes damage to the structure of the heart valves, such as mitral stenosis. One of the complications of severe mitral stenosis is thrombus in the left atrium. This condition is closely related to inflammation, so inflammatory cells such as lymphocytes and platelets are closely related to their severity and complications. Therefore, this study aims to see the ability of mitral platelet and lymphocyte ratios to the incidence of left atrial thrombus. Methods: This study is an analytical descriptive study with a cross-sectional research design, conducted at the Integrated Heart Center of Haji Adam Malik Hospital, from November 2024. The parameters of echocardiography, blood laboratory, as well as thrombus in the left atrium data were acquired. A statistical analysis test will be was done to assess the difference in the average ratio of platelets and lymphocytes based on the presence of thrombus in the left atrium, as well as the ability of the predictor of the ratio. Statistical analysis was carried out using SPSS software, a P value of < 0.05 was considered significant. Results: There are a total of 175 samples in this study. A total of 45 (25.7%) of the sample had thrombus in the left atrium. The median value and interquartile range of the Platelet/Lymphocyte Ratio (PLR) were higher in the thrombus group in the left atrium compared to the group without thrombus in the left atrium (P = 0.0001). The ROC curve analysis showed PLR parameters, with P = 0.0001, AUC 0.713, and 95% CI 0.620 – 0.806. The threshold value of PLR 132.5 has a sensitivity of 71.1% and a specificity of 61.0% has the ability to predict the presence of thrombus in the left atrium. Conclusion: The PLR ratio has a significant association with the occurrence of thrombus in the left atrium, in the condition of severe mitral stenosis due to rheumatic heart disease